Prognostic Impact of Red Cell Distribution Width on the Development of Contrast-Induced Nephropathy, Major Adverse Cardiac Events, and Mortality in Coronary Artery Disease Patients Undergoing Percutaneous Coronary Intervention - Latif, Azka; Ahsan, Muhammad J.; Lateef, Noman; Kapoor, Vikas; Fazeel, Hafiz Muhammad; Razzaq, Faryal; Iftikhar, Ahmad; Ashfaq, Muhammad Zubair; Anwer, Faiz; Mirza, Mohsin; Kabach, Amjad (Current Cardiology Reviews, 2021)
Red cell distribution width (RDW) serves as an independent predictor towards the prognosis of coronary artery disease (CAD) in patients undergoing percutaneous coronary intervention (PCI). A systematic search of databases such as PubMed, Embase, Web of Science, and Cochrane library was performed on October 10th, 2019, to elaborate the relationship between RDW and in hospital and long term follow up, all-cause and cardiovascular mortality, major adverse cardiac events (MACE) and development of contrast-induced nephropathy (CIN) in patients with CAD undergoing PCI. Twenty-one studies qualified this strict selection criterion (number of patients = 56,425): one study was prospective, and the rest were retrospective cohorts. Our analysis showed that patients undergoing PCI with high RDW had a significantly higher risk of in-hospital all-cause mortality (OR 2.41), long-term all-cause mortality (OR 2.44), cardiac mortality (OR 2.65), MACE (OR: 2.16), and odds of developing CIN (OR: 1.42) when compared to the patients with low RDW. Therefore, incorporating RDW in the predictive models for the development of CIN, MACE, and mortality can help in triage to improve the outcomes in coronary artery disease patients who undergo PCI.
Keywords: major adverse cardiac events